Caramel pecan roll murder - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery., 2022)
"Embracing a sweet escape from her usual routine at The Cookie Jar, Hannah gets asked for her help in baking pastries at the local inn for a flashy fishing competition with big prizes and even bigger names. But the fun stops when she spots a runaway boaton the water and, on board, the lifeless body of the event's renowned celebrity spokesperson...Famed TV show host Sonny Bowman wasn't humble about his ability to reel in winning catches, and no one knew that better than his tragically overworked sidekick,Joey. Did Joey finally take bloody revenge on his pompous boss-or was Sonny killed by a jealous contestant? With goodies to bake and a mess of fresh challenges mixed into her personal life, it's either sink or swim as Hannah joins forces with her sister,Andrea, to catch a clever culprit before another unsuspecting victim goes belly up..."--